STUDI PENDAHULUAN UNSUR TANAH JARANG PADA LEMPUNG BERSISIK MÈLANGE BOBONARO DI DESA OBEN, KECAMATAN NEKAMESE, KABUPATEN KUPANG, PROVINSI NUSA TENGGARA TIMUR - Kotta, Herry Zadrak; Mella, Welhelmus; Suwari; Banunnaek, Noni (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2024)
The location of the investigation area is in Oben Village, Nekamese District, Kupang Regency, East Nusa Tenggara Province with coordinates 123° 40'40” E - 123° 41'20” E and 10° 16'0” S - 10° 16'40” S. The geology of the study area is generally occupied by mixed rocks dominated by a gray clay, blackish brown, reddish brown, with foreign chunks consisting of peridotite, sedimentary rock consisting of brown and reddish reddish limestone, silt, micaceous sandstones, metamorphic rock: chlorite schist, with quartzite veins. Of the five samples analyzed, namely four samples of soil matrix and one sample of Peridotite, the following results were obtained: six rare earth elements were contained in 4 samples of the soil matrix, namely Yttrium (Y): 3.63 – 68.75 ppm, Praseudymium (Pr): 7.38 – 38.38 ppm, Scandium (Sc): 4.83 – 4.93 ppm, Lanthanum (La): 21.48 – 91.03 ppm, Cerium (Ce): 32.48 – 184.85 ppm, and Neodymium (Nd): 9.4 – 57 ppm specifically for sample 1 also contains 3 rare earth elements, namely: Gadolinium (Gd): 3.48 ppm concentration the average is lower than its abundance in nature, Samarium Sm: 13.1 ppm, and Dysprosium: (Dy): 6.88 ppm. For rock samples only contain Praseudymium (Pr): 7.78 ppm and Cerium (Ce): 87.88 ppm.